2020
DOI: 10.1080/02670844.2020.1742469
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance of steel guideway with biomimetic hexagonal micro-textures

Abstract: An Nd:YAG laser was used to fabricate biomimetic hexagonal micro-textures on the mating surfaces of steel guideways. The influence of the micro-textures under grease lubrication on the tribological performances of guideways was determined using a guideway reciprocating sliding tester facility for different micro-textures distributions and orientations, loads and sliding speeds. Results revealed that biomimetic hexagonal micro-textures had a positive influence on the tribological properties of guideway when onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…While the texture ratio is high, the lubricant spreading speed will be low and the storage amount between the friction interfaces is small, which also results in a high COF. In additional, This hexagonal orientation friction properties are consistent with the the results of Yun Zhang et al 21 and Yinghui Zhong et al 35 Their results show that the bearing capacity in the TV direction is larger than that in the TP direction, potentially resulting in a reduced COF.…”
Section: Resultssupporting
confidence: 88%
“…While the texture ratio is high, the lubricant spreading speed will be low and the storage amount between the friction interfaces is small, which also results in a high COF. In additional, This hexagonal orientation friction properties are consistent with the the results of Yun Zhang et al 21 and Yinghui Zhong et al 35 Their results show that the bearing capacity in the TV direction is larger than that in the TP direction, potentially resulting in a reduced COF.…”
Section: Resultssupporting
confidence: 88%
“…Equation (2) shows that the modification of the guideway can be achieved by controlling the dwell time.…”
Section: Optimization Of Combined Processingmentioning
confidence: 99%
“…Steel is cheap and is extensively used as guideway material, but the machining accuracy is affected by force and thermal deformation during the processing of steel guideways. Therefore, steel guideways are rarely used on ultra-precision moving platforms [ 2 ]. Wang [ 3 ] carried out the experimental analysis on trial production of 45 steel inlaid guideways.…”
Section: Introductionmentioning
confidence: 99%
“…But later application showed that micro bulges’ wear resistance was poor. Deng Jianxin and his colleagues fabricated micro grooves (Yue et al , 2019) and hexagonal textures (Zhang et al , 2020) on guideway surface in a simplified guideway apparatus. In Yue’s study, they found textures enhance resistance of stick-slip phenomenon by improving oil film retainability.…”
Section: Introductionmentioning
confidence: 99%